Implementasi dan Eksistensi Khiyar (Studi Transaksi Jual Beli melalui Marketplace) - Nubahai, Labib (Sharia Faculty Islamic Economic Law Study Department, 2023)
This research aims to analyze the implementation and existence of khiyar in buying and selling transactions through marketplaces. This study uses a qualitative approach with a descriptive analysis method. The results of this study indicate that in practice, buying and selling transactions through marketplaces have implemented khiyar. However, in terms of knowledge and literacy, both buyers and sellers have not fully understood khiyar. Some factors or obstacles that hinder the implementation of khiyar in buying and selling transactions through marketplaces include laziness, lengthy processes of product or fund returns, lack of socialization about religious knowledge, neglect of contractual obligations in buying and selling, and lack of awareness and empathy. The position of the concept of khiyar in modern times is relative. The existence of khiyar can be known through the position of the buying and selling contract. Khiyar is considered as a complementary condition, which means that the presence or absence of khiyar in the buying and selling contract does not affect the validity of the contract itself because khiyar cannot stand alone without the existence of the buying and selling contract as the main contract. However, khiyar is recommended as the best solution to strengthen the position of the contract, making it more ideal and achieving benefits for both parties involved in the transaction.